Influence of electrolyte nature on electrochemical properties of carbon material of plant origin - Ihor Semkiv; Vitalii Vashchynskyi; Andrii Kashuba; Hryhorii Ilchuk; Mykola Solovyov (Tekhnologiya i Konstruirovanie v Elektronnoi Apparature)
Non-aqueous electrolytes are advantageous for power sources due to the increase in the operating voltage since their electrochemical stability range is much wider. It should be noted that the capacitor's capacitance depends on the capacitance provided by the electrode material, expressed in F/g, while its voltage and resistance depend on the electrolyte. Therefore, it is very important to study the electrochemical properties of carbon material in aqueous and organic electrolytes and to determine the effect of the electrolyte on the capacitance of the capacitor formed on its basis. The cathode mixture was made of porous carbon material obtained from biomass and a binding additive. Then, it was pressed onto a nickel grid with an area of 0,5 cm2. A 30% aqueous solution of potassium hydroxide (KOH) and a 0,7-molar solution of tetraethyl ammonium tetrafluoroborate ([C2 H5 ]4 NBF4) in acetonitrile (CH3CN) was used as the electrolyte. The measurements were carried out using two- and three-electrode schemes with a silver chloride reference electrode. Modeling impedance data to equivalent electrical circuits has assisted to establish the influence of the volume charge region in the electrode material on the capacitor's capacitive characteristics. The specific capacitance values of 125 F/g in KOH and 101 F/g in [C2 H5 ]4 NBF4 are determined by the electrolyte type used and the nature of salts and bases dissolved in it. The practical significance of the obtained results is the application of the developed methods for obtaining carbon material with developed micro- and mesoporous structures and improved physicochemical properties.